Implementasi Strategi Branding Guna Memperkuat Brand Image dan Brand Value CV Mandiri Kopi - Manurung, Agustina Dian Putri; Trisatya, Achmad Afriadi; Adiputra, Achmad Basyir Santoso; Hazmi, Fadli; Purba, Murdhiyati Hilma; Rauziqmi, Rosi (Yayasan Cita Cendikiawan Al Kharizmi, 2022)
A business certainly must have a strong branding strategy in order to realize the vision and mission of a business. In the midst of an increasingly massive market growth and development, of course this has an impact on the increasing number and development of various businesses in the community, including the coffee business. The coffee business is growing well from upstream to downstream. More and more similar businesses make the competition tougher and of course a good branding strategy is needed. The strengthening of brand value and brand image in terms of can strengthen the purchase intention by consumers. This community service program is expected to be able to provide assistance to the coffee business of CV Mandiri Kopi so that it can strengthen the brand and is expected to increase coffee sales. Keywords: brand value, brand image, and purchase intention.